We are willing to pay to support wetland conservation: local users' perspective - Kaffashi, Sara; Shamsudin, Mad Nasir; Radam, Alias; Abdul Rahim, Khalid; Yacob, Mohd Rusli (Taylor & Francis, 2013)
The main objective of this study is to elicit the benefits that arise from Shadegan wetland in southern Iran to the users of this ecosystem, who are impacted most significantly by degradation/conversion of this ecosystem. Hence, a choice experiment (CE) and contingent valuation method (CVM) survey of users of the Shadegan wetland were conducted to estimate the value of non-market services provided by the wetland. The benefits from high-level conservation of the wetland are estimated from CVM to be about US$ 2.26 per household of users. Meanwhile, the estimated compensated surplus from CE was about US$ 8.28. Findings of this study suggest that the high value of Shadegan wetland for user communities can help policy-makers and wetland managers adopt policies that have no further conversion benefits than conservation or risks of degradation.